Food miles and food choices: the case of an upscale urban hotel in Hong Kong. Issue 6 (3rd June 2017) - Pratt, Stephen; Mackenzie, Murray; Lockwood Sutton, Jonathon
ABSTRACT: The nature of food production and consumption has changed dramatically in recent decades. Food sources for hotels and resorts have been an increasingly important sustainability topic in recent years. Where food is sourced has important implications for the economic, environmental and socio-cultural sustainability of tourist destinations. Based on where food is sourced and the mode of transportation, food miles is calculated for an upscale urban hotel in Hong Kong over a 12-month period. Greenhouse gas emissions associated with these food miles are computed. Over three-quarters of the food and beverages procured travelled via sea, the most energy efficient mode of transportation. Follow-up interviews with the hotel's procurement and executive chefs reveal the motivation behind these purchase decisions. While quality of food is the main driver for chefs, the procurement department take quality and cost into consideration. These different motivations provide potential conflict in sourcing food sustainably. Another issue raised is that food being procured from nearby countries may have questionable health and safety standards. Just because food can be procured closer to the destination does not necessarily mean it is the most sustainable option.